"The Heartbeat of Equity: "The Crucial Contributions of Nurses in Health Equity" - muna salahat (Jordan University of Science and Technology, 2024)
Background: Healthcare equity is a critical issue; it goes beyond providing equal access to healthcare services. It includes addressing mental, social, and educational needs. The health equity aims to eliminate health disparities that influence marginalized populations. Purpose: The aim of this paper was to conduct an in-depth analysis of the concepts of health equity and disparities in healthcare, with a focus on nursing perspectives. Additionally, the paper aimed to emphasize the critical role played by nursing professionals in promoting health equity and eliminating health disparities. Method: A scoping review was performed to determine applicable international reports and literature published in English. The search was conducted across various electronic databases, including Google Scholar, CINAHL, EBSCO, MEDLINE, and PubMed. Results: To address the prevalent health disparities, urgent action is needed at both the national and international levels. Achieving health equity requires collaboration across various societal sectors to address the root causes of health inequities because no single entity can address them. Although the manifestation of health inequities may differ globally, there are shared challenges that require comprehensive approaches to tackle underlying causes. Undoubtedly, nurses play a vital role in addressing health equity. Conclusion: Nurses play multifaceted roles in promoting health equity through technology, policy, education, research, philosophy and theory context, and disaster. They have the opportunity to address health disparities and promote health, particularly in underserved communities.